Drafting Extension of Time for Completion to Avoid Time at Large in Construction Contract - Irsan; Utama, Meria; Nurliyantika, Rizka; Saputra, Ricky; Idris, Akhmad (Notaire, 2024)
In a construction contract, there are potential delays in the project, and both parties try to avoid this situation. For the reason, the customary in construction contracts to state a completion date by which the works must be completed. This is usually based on an estimate of how long the project will take or may be determined by the date when the employer wants the project to be completed. To answer the above problems, the method used is normative legal research. The objective of this research was to understand clearly and holistically the complexities of construction contracts. Some contractors request an extension of time to finish the duty because delay, which fails to complete on time, is generally referred to as a critical situation. The worst situation happens if it is not stipulated in a construction contract, and it can eliminate the contractor's obligation to complete the work promised or create a condition called "time at large.” Of course, this is very undesirable for the owner. Especially if the contractor who carries out work is a foreign company, it certainly adds to the complexity of this condition. Therefore, to avoid this, it is essential to ultimately make an extension of time clause in an international construction contract.